Calcium-based mixed oxide catalysts for transesterification of palm oil to biodiesel - Wong, Yong Chen (2014)
Rapid population growth and industrial revolution have resulted in non-renewable energy natural resources scarcity on a global scale and global warming. The energy crisis issue and environmental awareness have urged the development of cleaner alternative fuels. Biodiesel, a renewable energy with biodegradable characteristic showed a great potential to be explored to satisfy the world energy demand while simultaneously maintain the sustainability of the environment. In this study, various calcium-based mixed oxide catalysts were studied and evaluated to develop an effective catalyst with high activity and durability for biodiesel production process. Investigations were carried out on different compositions of calcium and niobium (CaO-Nb2O5), calcium and cerium (CaO-CeO2), and, calcium and nickel (CaO-NiO) mixed oxides. These catalysts were characterized by x-ray diffraction (XRD) analysis, thermal gravimetric analysis (TGA), Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), x-ray fluorescence (XRF) spectroscopy, temperature-programmed desorption of CO2 (TPD-CO2) and nitrogen sorption with Brunauer-Emmett-Teller (BET) surface area analysis. The catalytic activities of the mixed oxides were tested by transesterification of palm oil. Effects of reaction time, methanol to oil ratio, reaction temperature and the amount of catalysts were investigated to optimize the yield of fatty acid methyl esters (FAME). The optimum FAME yield, 96 %, was observed in CaO-Nb2O5 system when the reaction mixture were refluxed in the condition of 65 oC with methanol to oil ratio equal to 12, a reaction time of 2 h, and 3 wt.% of catalyst. Meanwhile, under optimum conditions of 5 wt. % catalyst loading, 12:1 methanol to oil molar ratio, and 65 oC reaction temperature, CaO-CeO2 and CaO-NiO mixed oxides produced biodiesel yields of 95 % and 91 %, respectively, but with a reaction time of 4 h and 3 h, respectively. In term of durability, CaO-Nb2O5, CaO-CeO2 and CaO-NiO mixed oxides can be reused 6, 6 and 5 times, respectively without significant losses of catalytic activities (FAME yield > 70 %). Pores filling and lixiviation of calcium into the reaction medium and products are the major factors for the deactivation of catalysts. Biodiesel production was optimized by using response surface methodology (RSM) in conjunction with central composite design (CCD). It was found that CaO-Nb2O5 achieved an optimum level of biodiesel yield, 97.05 % at 2.49 h reaction time, 3.54 wt. % of catalyst loading and methanol to oil molar ratio of 13.20. Meanwhile, CaO-CeO2 achieved optimum biodiesel yield of 96.39 % under the following reaction conditions: reaction time: 3.67 h, catalyst amount: 4.03 wt. %, methanol to oil molar ratio: 14.17. Besides, under the reaction conditions: reaction time: 3.73 h, catalyst amount: 3.34 wt. %, methanol to oil molar ratio: 12.23, the optimum biodiesel yield achieved by CaO-NiO catalyst was 92.93 %. In a nutshell, although pure calcium oxide shows the promising results in biodiesel production, it tends to leach out into the reaction medium and products. However, the mixed oxides prepared in this study greatly improve the performance and stability of the calcium by reducing its lixiviation into reaction medium and products. Among the three mixed oxides, CaO-Nb2O5 and CaO-CeO2 mixed oxides are the best catalysts for transesterification process, either in terms of biodiesel yield (≥ 95 %) or the stability of the catalysts (both can be reused 6 times). Therefore, these catalysts are the potential substitute for the current applied homogeneous catalysts (NaOH, KOH) in the biodiesel industry, where no post-treatments of biodiesel are needed and thus it is more environmentally benign.